2016
DOI: 10.1097/acm.0000000000001250
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Academic Compensation by Gender: A Follow-up to the National Faculty Survey Cohort Study

Abstract: Disclaimer: The opinions expressed in this article are those of the authors alone and do not reflect the views of the National Institutes of Health, the funders of this study. None of the funders were involved in the design of the study; the collection, analysis, and interpretation of the data; or the decision to approve publication of the finished manuscript.Previous presentations: National Meeting of the Society of General Internal Medicine, San Diego CA, April 18, 2014. HHS Public Access Author Manuscript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(59 citation statements)
references
References 24 publications
(26 reference statements)
1
58
0
Order By: Relevance
“…The current literature on implicit bias suggests that everyone, including physicians, 25 , 26 , 27 , 28 , 29 has unconscious ways of operating that might affect who we value in any process, including the solicitation of authors for perspective-type articles or selection of authors for publication from among those offering unsolicited submissions. Indeed, implicit bias has been cited as a potential underlying factor associated with gender-related workforce disparities, 23 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 and, in this case, institutional bias may in part be due to editors’ unconscious preference for men authors. As implicit bias is unconscious, it is imperative to avoid blaming individuals for their inability to recognize it and instead focus on developing metrics-driven processes that support equitable inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature on implicit bias suggests that everyone, including physicians, 25 , 26 , 27 , 28 , 29 has unconscious ways of operating that might affect who we value in any process, including the solicitation of authors for perspective-type articles or selection of authors for publication from among those offering unsolicited submissions. Indeed, implicit bias has been cited as a potential underlying factor associated with gender-related workforce disparities, 23 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 and, in this case, institutional bias may in part be due to editors’ unconscious preference for men authors. As implicit bias is unconscious, it is imperative to avoid blaming individuals for their inability to recognize it and instead focus on developing metrics-driven processes that support equitable inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Institutional policies such as tenure clock ''pauses'' for parental leave, as well as equal parental leave policies for both male and female caregivers, may help reduce these disparities, especially as income disparities between men and women academics may be attributed to differences in taking time off. 32 It is heartening that while women were underrepresented at all but the entry-level academic rank, women academics at each rank graduated more recently from training than their male counterparts. This pattern is different than what has been noted in other medical disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey showed that 35% of academic medical institutions did not have programs in place to support recruitment, promotion, and retention of women. 15 Training in negotiation skills, 16 education about implicit bias, 17 , 18 coaching and mentoring, and financial support for professional development programs may further promote a supportive environment for women. 13 Additionally, institutions must commit to integrating women into leadership roles.…”
Section: Discussionmentioning
confidence: 99%